Anatomical structures of the limb of white-nest swiftlet (Aerodramus fuciphagus) and white-headed munia (Lonchura maja) - Abu Bakar @ Zakaria, Md Zuki; M. M., Abdul Ghani; Khadim, Khalid Kamil; Abdul Razak, Intan Shameha; Mat Isa, Kamaruddin (Universiti Putra Malaysia Press, 2012)
The main aims of this study were to examine the anatomical structures of the pelvic limb of white-nest swiftlet and to find the reason why the birds are not able to walk, stand and perch while standing. The findings were compared with the white-headed munia which has almost similar body weight and appearance, and the above-mentioned abilities. Four left limbs from each type of the birds were examined macroscopically under the stereomicroscope, whereas the bones and muscles of both the species were measured and compared. The lengths of the femur and tibial bones of the two species were not significantly different, although the metatarsal bone and digits of the white-nest swiftlet were found to be shorter than those of the white-headed munia. In particular, the digits of the white-nest swiftlet were shorter and curvy as compared to the white-headed munia which has longer digits with straight and sharp claws. The limb muscles of white-nest swiftlets were smaller and thinner than the white-headed munia. Four muscle groups, namely, bicep femoris, semimembranous, semitendinosus and gastrocnemius, were also taken from each bird for histological examination. The muscle sections were stained with Haematoxylin and Eosin. Histologically, the white-nest swiftlets have relatively smaller muscle groups and muscle bundles as compared to the white-headed munia. Thus, the limb is weak and unable to support its body weight. In conclusion, apart from the short metatarsal bone and digits, the small muscles of the limb could be the main reason for the inability of the white-nest swiftlets to use their limbs for walking, standing and perching while standing.